Nursing outcomes classification (NOC) - Moorhead, Sue (Mosby Elsevier, 2008)
Nursing Outcomes Classification (NOC) presents standardized terminology and measures for nursing-sensitive outcomes that result from nursing interventions. Representing more than 16 years of work by the research team at the University of Iowa, the Classification was developed to be used by clinicians, students, educators, researchers, and administrators in a variety of clinical, educational, and research venues. The comprehensiveness of the outcomes and the inclusion of specific indicators that can be used to evaluate and rate the patient in relation to outcome achievement make this book an invaluable resource for both practicing nurses and students.--Anotace od vydavatele